Look at Detroit: The United Auto Workers and the Battle to Organize Volkswagen in Chattanooga. (3rd September 2019) - Minchin, Timothy J.
ABSTRACT: On February 14, 2014, workers at Volkswagen's new plant in Chattanooga, Tennessee, voted 712 to 626 against being represented by the United Automobile Workers of America (UAW). The result capped one of the most high-profile organizing campaigns of recent years, with most media accounts anticipating a UAW victory, especially as VW had declared that it would not oppose the union. The VW election is also now attracting scholarly interest, with accounts stressing the role of external opposition – especially from conservative politicians and lobby groups – along with the UAW's over-reliance on partnerships with German actors. Providing a detailed analysis of the campaign, this article recognizes the importance of these factors, but also argues that an important role was played by the UAW's strong association with the domestic automakers, and especially with Detroit, their historic base. Citing the fact that foreign automakers had expanded since the 1980s while the domestics had contracted, opponents effectively linked the UAW with economic decline. These arguments swayed many workers. Placing the VW story within the broader struggle of the UAW to organize a foreign-owned auto plant, the article also stresses structural obstacles, especially the location of Greenfield plants in areas of low union density.